MARKETING STRATEGY OF BETAWI SETU CULTURAL VILLAGE THROUGH SOCIAL MEDIA - Feriano, Dennis; Mustofa, Budiman Mahmud; Wuryatmini, Prihatni (UI Scholars Hub, 2021)
This paper discusses how the Setu Babakan Betawi Cultural Village in marketing tourist attractions through social media. This research uses qualitative research supported by quantitative data. The data collection techniques in this final project are observation, interviews, literature study, and questionnaire. The results of this study suggest that Setu Babakan Betawi Cultural Village Activities Unit to further improve marketing especially through social media, multiply activities that are inviting many visitors, overcome negative responses that still exist in the community regarding Setu Babakan Betawi Cultural Village, and improve hospitality and conduct training for tour guides which will be provided in the future.